2014
DOI: 10.4236/ojvm.2014.410025
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Avian Pathogenic <i>Escherichia coli</i> Strains from Broiler Chickens by Multiplex Polymerase Chain Reaction (PCR) and Random Amplified Polymorphic (RAPD) DNA

Abstract: We examined 50 Escherichia coli (E. coli) strains isolated from broiler chickens between January 2013 to March 2014 in order to evaluate the epidemiological prevalence of avian pathogenic E. coli (APEC) in Jordan by multiplex PCR and random amplification of polymorphic DNA (RAPD) tests. The multiplex polymerase chain reaction (PCR) which was used as tentative criteria of APEC targets 8 virulence associated genes; enteroaggregative toxin (astA), Type 1 fimbria adhesion (fimH), iron-repressible protein (irp2), P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
1
5
1
Order By: Relevance
“…The recovered results showed that presence of tsh in E. coli isolated from broiler chickens with respiratory manifestations at a percentage of 30% that agree with the result reported by Oh et al, (2011) who found that PCR for amplification of tsh gene of E. coli at a percentage of34.48% and lower than the result obtained by (Roussan et al, 2014) who identified tsh gene with a percentage (66%) by using PCR.…”
Section: Suspectedsupporting
confidence: 87%
See 1 more Smart Citation
“…The recovered results showed that presence of tsh in E. coli isolated from broiler chickens with respiratory manifestations at a percentage of 30% that agree with the result reported by Oh et al, (2011) who found that PCR for amplification of tsh gene of E. coli at a percentage of34.48% and lower than the result obtained by (Roussan et al, 2014) who identified tsh gene with a percentage (66%) by using PCR.…”
Section: Suspectedsupporting
confidence: 87%
“…This result is higher than the result that said by (Mbanga and Nyararai, 2015) who said that percent of PCR for amplification of fimH gene of E. coli was (33.3%) of APEC isolates and lower than the result obtained by (Roussan et al, 2014) who identified fimH gene with a percentage (94%) by using PCR.…”
Section: Suspectedcontrasting
confidence: 64%
“…On the other hand, APEC isolates can bind to avian tracheal cells and Type I fimbriae confer this ability. A study on APEC showed a 94% prevalence of fimH gene [ 33 ]. The fimH is claimed to be responsible for the first step in the colonization of the lungs and air sacs of birds.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli strains possess various virulence factors for extra-intestinal survival [4][5][6][7][8]. However, capacity to cause disease in a specific host species, depends on acquisition of appropriate virulence gene combination by a given E. coli strain [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, capacity to cause disease in a specific host species, depends on acquisition of appropriate virulence gene combination by a given E. coli strain [5]. The number of detected genes can be used as a reliable index of their virulence; and strains typed as APEC possess five to eight genes, while the non-APEC ones harbor less than four genes [5,8]. Virulence-associated genes, namely, iutA, hlyF, iss, iroN, and ompT were suggested as the minimum that can be used to identify an APEC strain with the highest pathogenicity [9].…”
Section: Introductionmentioning
confidence: 99%